Behçet's disease ocular attack score 24 and visual outcome in patients with Behçet's disease. Issue 7 (9th November 2015) - Tanaka, Rie; Murata, Hiroshi; Takamoto, Mitsuko; Ohtomo, Kazuyoshi; Okinaga, Kimiko; Yoshida, Atsushi; Kawashima, Hidetoshi; Nakahara, Hisae; Fujino, Yujiro; Kaburaki, Toshikatsu
Abstract : Aims: To investigate the ability of the Behçet's disease ocular attack score 24 (BOS24) scoring system to predict visual acuity (VA) in patients with ocular Behçet's disease. Design: This is a retrospective study. Methods: We included 91 eyes of 50 patients with ocular Behçet's disease (33 males, 17 females) who were referred to our hospital between 1986 and 2008 with >5 years follow-up. Total BOS24 scores over a 5-year period, BOS24-5Y, were calculated as the sum of BOS24 scores for each attack over the 5-year study period for each eye. Change in VA was defined as change in best-corrected visual acuity (BCVA) from the first remission to the last remission at the end of the target period. Factors related to change in VA (age, gender, BCVA at the first remission, total number of immunosuppressive medications and total number of ocular attacks during the 5-year period and BOS24-5Y) were evaluated using a linear mixed model. Results: BCVA (logarithm of the minimal angle resolution) deteriorated from 0.16±0.30 (mean±SD) to 0.21±0.37 over the 5-year study period, but there was no statistical difference. The total number of ocular attacks during the 5-year period and BOS24-5Y scores were 10.0±7.9 and 36.8±40.8, respectively. Linear mixed-model analysis revealed that BOS24-5Y was the most important index for VA deterioration, followed by BCVA at the first remission. Conclusions: BOS24-5Y was found to be a significant positive prognostic index for VA deterioration in patients with ocular Behçet's disease.